ANALISIS MINAT BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA KECAMATAN TOMPASOBARU KABUPATEN MINAHASA SELATAN - Jeremi Hendro Assa; Shelty Deity Meity Sumual; Allen A. Ch. Manongko (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study aims to analyze students’ learning interest and to identify the factors influencing it at SMP Negeri 3 Raraatean, Tompasobaru District, South Minahasa Regency. Students’ learning interest is an essential aspect of the learning process, as it directly affects students’ levels of engagement and the achievement of learning outcomes at the junior high school level. This research employed a qualitative approach with a case study design, focusing on an in-depth understanding of students’ learning experiences, perceptions, and learning conditions.Data were collected through observations, in-depth interviews, and documentation, involving students, teachers, parents, and the school principal as the main data sources. The collected data were analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and iterative conclusion drawing and verification. The findings indicate that students’ learning interest is at a moderate level and tends to be situational in nature. Learning interest increases when teachers apply varied, contextual, and interactive teaching methods, but tends to decrease in monotonous learning situations that provide limited opportunities for active student involvement.Internal factors influencing learning interest include intrinsic motivation, self-confidence, and students’ learning readiness, while external factors encompass teacher roles, parental support, the availability of learning facilities, and students’ social environment. These findings emphasize that enhancing students’ learning interest requires synergy among innovative instructional strategies, family involvement, and the creation of a supportive learning environment to foster sustainable development of students’ learning interest. ABSTRAK Penelitian ini bertujuan untuk menganalisis minat belajar siswa serta mengidentifikasi faktor-faktor yang memengaruhinya di SMP Negeri 3 Raraatean, Kecamatan Tompasobaru, Kabupaten Minahasa Selatan. Minat belajar siswa merupakan aspek penting dalam pembelajaran karena berperan langsung terhadap tingkat keterlibatan siswa dan pencapaian hasil belajar pada jenjang sekolah menengah pertama. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus yang berfokus pada pemahaman mendalam terhadap pengalaman, persepsi, dan kondisi belajar siswa. Pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi dengan melibatkan siswa, guru, orang tua, serta kepala sekolah sebagai sumber data utama. Data yang diperoleh dianalisis menggunakan model analisis interaktif Miles, Huberman, dan Saldaña yang meliputi proses reduksi data, penyajian data, serta penarikan dan verifikasi kesimpulan secara berulang. Hasil penelitian menunjukkan bahwa minat belajar siswa berada pada kategori sedang dan cenderung bersifat situasional. Minat belajar meningkat ketika guru menerapkan metode pembelajaran yang variatif, kontekstual, dan interaktif, namun cenderung menurun pada pembelajaran yang monoton dan kurang melibatkan siswa secara aktif. Faktor internal yang memengaruhi minat belajar meliputi motivasi intrinsik, kepercayaan diri, dan kesiapan belajar siswa, sedangkan faktor eksternal mencakup peran guru, dukungan orang tua, ketersediaan fasilitas belajar, serta lingkungan sosial siswa. Temuan penelitian ini menegaskan bahwa peningkatan minat belajar siswa memerlukan sinergi antara strategi pembelajaran inovatif, keterlibatan keluarga, dan penciptaan lingkungan belajar yang kondusif agar minat belajar dapat dikembangkan secara berkelanjutan.